Human Rights and Systemic Wrongs: National Preventive Mechanisms and the Monitoring of Care Homes for Older People. (30th March 2022) - Hardwick, Nick; Marriott, Jane; Mason, Karl; Steinbrecher, Marie
Abstract: Care homes for older people may become places of deprivation of liberty due to their residents' lack of capacity to consent to their stay. The Optional Protocol to the Convention Against Torture requires States Parties to establish National Preventive Mechanisms to undertake visits to all places of deprivation of liberty to prevent torture and other ill treatment. This paper discusses the ways in which National Preventive Mechanisms report on human rights concerns in older people's care homes across 26 Council of Europe states. A framework established by the European Committee for the Prevention of Torture provides a starting point for this analysis. Common themes around restraint, ill treatment, safeguards for involuntary placements, and resourcing issues emerge. Against a backdrop of concerns heightened by the Covid-19 pandemic, the paper concludes that a narrow focus on individual human rights needs to be supplemented by addressing the structural issues on which the more broadly conceived rights of residents of care homes for older people depend.